Poverty, insecurity, and climate change stare at the EU-AU relations - Vincent Patrick-Agulonye, Uzoma (2022)
The renewed relationship between the European Union (EU) and the African Union (AU) presents a platform for mutuality of benefits and responsibilities. Regional security is one area where both can learn based on recent and present experiences. The EU can learn from the AU from the post-Arab Spring arms proliferation, which led to internal conflicts, transborder crimes, and insurgency across Africa. The AU, on its part, can learn from the EU on civil governance, leadership, and transborder checks. The Regional Security Complex Theory aids our understanding of regional security. This paper examines some challenges confronting both regions and recommends panaceas of mutual benefits.